KNOWLEDGE, ATTITUDE AND PRACTICE OF MEDICAL ETHICS AMONG RESIDENT PHYSICIANS OF SPECIALTY CERTIFICATE IN ASEER PROVINCE, SAUDI ARABIA - Al-Shehri, Eman; Siddiqui, Aesha Farheen; Khalildr, Shams un Nahar (Journal of Liaquat University of Medical & Health Sciences, 2020)
OBJECTIVE: To assess the knowledge, attitudes and practices of medical ethics among resident doctors under Saudi commission for health specialties. METHODOLOGY: A cross sectional descriptive study was conducted in June to December, 2016 on a sample of 261 resident doctors, who were available on a predetermined date of interview. A self-administered questionnaire was used to collect data, which was analysed using SPSS 20. Frequencies and percentages were used for descriptive analysis. RESULTS: More than one third (35.6%) of the respondents have poor knowledge and only 20% had good knowledge of medical ethics. Regarding source of ethics knowledge, 27% residents reported experience and 15 % reported training during residency. More respondents had positive attitude in aspects of purpose of ethics, abandoning confidentiality, reporting examination findings as normal without doing the examination. Most of the respondents exhibited a positive attitude by disagreeing that doctors should accept commission by referring patients for investigations or taking incentives from drug companies. Only 25.6% respondents reported never having encountered unethical practices by team members while a good number reported having faced it sometimes and few (16.9%) reported frequent such encounters. CONCLUSION: The findings suggest that there are gaps in knowledge attitude and practice of medical ethics among the residents, underlining the importance of strengthening medical ethics education in Saudi Arabia.